Copper‐Catalyzed Cross‐Coupling of Thiols, Alcohols, and Oxygen for the Synthesis of Esters. Issue 3 (8th December 2014) - Lim, Seungyeon; Ji, Miran; Wang, Xi; Lee, Chan; Jang, Hye‐Young
Abstract: Copper‐catalyzed, one‐pot, three‐component coupling reactions using thiols, alcohols, and oxygen to form a variety of esters in good yields were studied. In the presence of easily oxidized benzylic and allylic alcohols, thiols were selectively oxidized to form thionoesters, which underwent facile S/O exchange to afford esters. Thiols may be used as an alternative benzoyl source under mild aerobic conditions. Abstract : Copper‐catalyzed coupling of thiols, alcohols, and oxygen provided a variety of esters through S/O exchange of thionoester intermediates